GREEN HUMAN RESOURCE MANAGEMENT AND SUSTAINABLE PERFORMANCE IN BUMDES: MEDIATING EFFECTS OF GREEN INNOVATION AND RISK MANAGEMENT - Ahmad Ahmad; Etik Prihatin; Heriyanti Mustafa; Firman Bachtiar; Danis Imam Bachtiar (Universitas La Tansa Mashiro, 2026)
Rapid economic development and environmental degradation have become major challenges for community-based organizations, including Village-Owned Enterprises (BUMDes) operating in the tourism sector. Tourism-based BUMDes in Banten Province not only function as drivers of local economic development but also carry responsibilities for maintaining environmental and social sustainability. Therefore, the implementation of Green Human Resource Management (GHRM) practices has become a crucial strategic approach for enhancing the sustainable performance of tourism-based BUMDes. Existing literature indicates that GHRM practices integrated with green innovation can foster environmentally responsible work behavior and generate sustainable value. However, risk management in the development of village-based tourism remains relatively limited and has not been optimally integrated with GHRM practices and green innovation initiatives. Based on this gap, the present study aims to analyze the influence of GHRM practices on the sustainable performance of tourism-sector BUMDes in Banten Province through the mediating role of green innovation. Additionally, this study examines the moderating role of risk management in the relationship between GHRM practices and sustainable performance. This study adopts a quantitative research approach. Data were collected from managers and employees of tourism-sector BUMDes in Banten Province. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the structural relationships among the variables. The results reveal that GHRM practices positively influence sustainable performance through green innovation. Furthermore, risk management significantly moderates the relationship between GHRM practices and green innovation in enhancing sustainable performance. These findings provide important implications for BUMDes managers, local governments, and policymakers in designing sustainable, competitive, and environmentally responsible strategies for village tourism development.